Analytical strategies to identify and quantify organic admixtures in functionalized mineral model systems. Issue 3 (9th January 2019) - Hahn, Dominik; Sax, Almuth; Quirmbach, Peter; Faure, Jean‐Michel; Benyahia, Kamel; Wöhrmeyer, Christoph; Parr, Chris
Abstract: This study describes an analytical approach to identify and quantify organic admixtures, which are increasingly being used in multifunctional additive systems, such as calcium aluminate cement‐based dry mix formulations. The investigations refer to a wide range of established organic admixtures used in high performance industrial concrete applications, such as flow agents, retarders, or organic plasticizers, which are added in dosages of up to 5% (to the mass of cement). Based on specific considerations, a consistent approach was outlined by combining the output of complementary analytical techniques. These analytical methods included Thermogravimetric Analysis and Differential Scanning Calorimetry coupled with Mass Spectrometry, in combination with Fourier Transform Infrared Spectroscopy and Morphologically Directed Raman Spectroscopy, as well as Total Carbon Analysis. Within the scope of the aforementioned studies, the applied methods were validated for stringent detection limits (LOD < 0.05%) and precision demands (SD 1% to 7% with R 2 > 0.99).